2022
DOI: 10.29165/ajarcde.v7i1.190
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Fermented Livestock from Agricultural Waste to the Bhakti Pertiwi Cattle Group, Belimbing Village, Pupuan District, Tabanan Regency

Abstract: The Provincial Government of Bali continues to encourage community farmers to form livestock groups, especially cows through the Integrated Agricultural System (“Simantri”) program since 2009/2010 which is now known as the Integrated Agricultural System (Sipadu). In addition to the program, livestock groups are also formed independently by breeders spread across Bali, one of which is the “Bhakti Pertiwi” livestock group in Belimbing Village, Pupuan-Tabanan which was only formed in 2021. Assistance in empowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Based on the description of the research results above, it shows that giving fermented coffee skins can meet the crude protein needs needed by goats for the formation of cells and tissues in the body to increase their growth. The crude protein content in coffee skins fermented using LMO increases the crude protein content from 8.6 -9.5% to 17.67% [4], higher than forage grass and sufficient microelements. Meanwhile [7] states that the nutritional content of coffee skin fermented solidly contains nutrients including dry matter 97.987, protein 13.920, crude fiber 16.368, crude fat 6.179, organic matter 75.096, ash 23.051, and water content 2.013.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the description of the research results above, it shows that giving fermented coffee skins can meet the crude protein needs needed by goats for the formation of cells and tissues in the body to increase their growth. The crude protein content in coffee skins fermented using LMO increases the crude protein content from 8.6 -9.5% to 17.67% [4], higher than forage grass and sufficient microelements. Meanwhile [7] states that the nutritional content of coffee skin fermented solidly contains nutrients including dry matter 97.987, protein 13.920, crude fiber 16.368, crude fat 6.179, organic matter 75.096, ash 23.051, and water content 2.013.…”
Section: Resultsmentioning
confidence: 95%
“…Besides that, livestock also needs calcium and phosphorus content [3]. From the results of research [4] trials of coffee skin waste fermentation using several types of probiotics, namely EM-4, Bio Bali Tani, Aspergillus niger, and local micro-organisms (LMO) coffee skins concluded that fermentation of skin waste. This coffee can significantly improve the quality of coffee skin waste, especially the crude protein (CP) content.…”
Section: Introductionmentioning
confidence: 99%